Assessment of Parkinson disease quality measures on 12-month patient outcomes - Martello, Justin (Neurol Clin Pract, 2020)
BACKGROUND: Quality measures (QMs) exist to operationalize guidelines by measuring adherence to guidelines through documentation, ultimately leading to improved patient outcomes. Studies are rare looking at the relationship between adherence to Parkinson disease (PD) QMs and patient outcomes. METHODS: We assessed adherence of our movement disorders specialists (MDSs) to the American Academy of Neurology's 2010 PD QM set through chart review using the measure set work group's criteria of documentation. We then evaluated patient outcomes to see whether there was a correlation with adherence to these QMs. RESULTS: Ninety-seven consecutive patients met the inclusion criteria. The mean disease duration was 9.3 (5.8) years. All patients were assessed by 1 of 4 MDSs. A total of 68% of QMs were documented across all patients. There was a small positive correlation between the number of documented QMs the year before the index visit and the number of calls/emails both the year before and after the index visit (r = 0.20, p = 0.04 and r = 0.26, p = 0.01, respectively.) There was a small negative correlation between the number of documented QMs and the number of PD follow-up visits the year after the index visit (r = −0.19, p = 0.05.) No other outcome showed a statistically significant correlation with the adherence to documented QMs. CONCLUSIONS: We found no clinically important improvement in patient outcomes with higher adherence levels. It is important that QM developers validate QMs to ensure that they fulfill the intended goal of improved patient outcomes.